Point-prevalence of depression and associated risk factors - RICHARDS, DEREK (My University, 2014)
The study aimed to assess levels of depressive symptoms and associated risk factors in a sample of students in Bogotá, Colombia. A convenient sample (N = 254) of students at the University Antonio Nariño, Bogotá was invited to complete an online survey that contained questions associated with common risk factors for depression and the Beck Depression Inventory (BDI-II). Chi-square was used to analyze comparisons between demographic and risk factors and severity of depression, and comparisons between those depressed and not depressed. Odds Ratios and their 95% confidence interval (95% CI) were computed through logistic regression model developed for each independent variable. The point-prevalence of current depressive symptoms was 36.2%; women 47.3% and men 21.3%. Risk factors associated with depression included being a woman, having a previous diagnosis, suicidal ideation and (or) intent, sleep problems, a recent loss, and a history of family depression and alcoholism. The study confirms the high incidence of depression and associated risk factors in students. The results demonstrate a need for prevention measures, early detection and early intervention.
PUBLISHED
Keywords: DEPRESSION; Creative Technologies; Health, Clinical and Counselling; Psychology